Uprooted - Novik, Naomi (New York : Del Rey, 2015)
The corrupted Wood stands on the border of Agnieszka's valley home. Her people rely on the wizard known as the Dragon to contain its powers. But he demands a terrible price for his help: one young woman handed over to serve him for ten years.
Keywords: Wizards -- Fiction; Dragons -- Fiction; Young women -- Fiction; Friendship -- Fiction; Villeinage -- Fiction; Slavery -- Fiction; Peonage -- Fiction; Serfdom -- Fiction; Fantasy fiction